Variation in Amino Acid Contents of White and Red Sword Bean [Canavalia gladiata (Jacq.) D.C.] - Kwang Kim1, Jae; Ju Bong2, Sun; Un Park2, Sang (Asian Journal of Chemistry, 2016)
Sword bean (Canavalia gladiata) belongs to the genus Canavalia, a neglected group of legumes with many valuable characteristics, in addition to containing a variety of amino acids. The present study investigated amino acid variation in different cultivars of white and red sword bean. Twenty-one different amino acids were identified from different cultivars of white and red sword bean and levels of these amino acids varied significantly depending on the cultivar. The white sword bean cultivar had a total amino acid concentration that was 1.54 times higher than red sword bean. White sword bean contained higher levels of nine different amino acids, whereas red sword bean contained higher levels of 12 different amino acids. Among amino acids, glycine concentrations were the highest irrespective of cultivar. The range of glycine was 2616.73 to 4363.12 mg/100 g the dry weight of each cultivar. The sword bean cultivar contained 1.67 times higher levels of glycine than that of red sword bean. The amino acids found in the highest quantities in white sword bean varied marginally compared to red sword bean. However, in red sword bean, the amino acids found at higher levels varied widely compared to those of white sword bean. The results of this study demonstrate that sword bean cultivars contain varying amounts of amino acids, suggesting that these vegetable cultivars have the potential of serving as excellent sources of amino acids.